Tinjauan Yuridis Terhadap Pendirian Yayasan Pendidikan Sebagai Kegiatan Usaha Yang Bersifat Komersil Berdasarkan Undang-Undang Nomor 16 Tahun 2001 Tentang Yayasan Jo. Undang-Undang Nomor 28 Tahun 2004 - Riska Septiari; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The Foundation is a collection of a number of people organized and in terms of its activities, more as a social institution. Article 1 (1) of Law Number 16 of 2001 mentioning purpose of the foundation is to achieve certain objectives in the social, religious and humanitarian who has no members. Problems in this thesis includes two (2) things: is a social institution foundations can be categorized as a business entity and how the legal effect of an education foundation whose business activities are commercial. The general objective of this research is to fulfill the requirements and the final project to obtain a law degree at the Faculty of Law, University of Riau, increase knowledge of science, especially in the field of civil law.This research is using normative type of research which means this study conceptualized as what is written in the legislation. Analysis of materials research in the thesis using qualitative methods, in order to draw conclusions using deductive metode.This research has a descriptive nature, which is a form of research that aims to create a picture of the problem. Source of data used is secondary data of primary legal materials, secondary and tertiary. Datametode collection techniques literature studies or study documents such as books, magazines, journals and the legislation in force. Thus, this study has the relationship between the data contained either in the legislation or in the literature.This study shows that the foundation as a social institution can not be said as a business entity, but the foundation can establish an enterprise and / or participate in a business entity, as set out in Article 3 (1) of the Law Foundation. The legal consequences for the foundation for the business activities of a commercial character is if they are carried out in the activities of the foundation then does the liquidation or dissolution of the foundation's because according to the provisions of Article 62 paragraph (2) of the Law Foundation. Foundation as a social institution should not be associated with any company or entity because it would have violated the original purpose of the foundation is for the purpose of social, religious and humanitarian. Against the foundation seeking personal gain or commercial activities of the foundation by running checks should be done in order to know the truth and immediately dissolved if it violates the law.Keywords: Education Foundation- Operations- Commercial